The Role of Artificial Intelligence in Military Education: A Double-Edged Sword - Hendriman Putra; Budi Eko Mulyono (Indonesian Journal of Educational Science and Technology, 2024)
This study aims to analyze the paradoxical implications of artificial intelligence (AI) in military education, focusing on its potential benefits and drawbacks. A qualitative research approach, involving a review of relevant literature and analysis of military education policies related to technology integration, was employed. Findings indicate that AI can significantly enhance training effectiveness, personalize learning experiences, and streamline data management. However, concerns such as privacy breaches, overreliance on technology, and the decline of fundamental military skills have also emerged. Implications of this research are expected to provide insights for policymakers in developing more effective military education policies.